(untitled) (Mongolian Journal of Humanities and Social Sciences, 2024)
This research aims to analyze the structure and unity of paragraphs written by undergraduate students at Mongolian National University of Education. The study utilizes the structural components and unity of English paragraphs as a framework. Six students participated in the study, with research data comprising essays in English covering various topics. The findings reveal that students struggle to grasp the concept of a paragraph as a distinct section of writing, typically focusing on a single theme to express a coherent idea about an event. Many students encountered difficulties in composing the structural elements of a paragraph, including crafting a topic sentence, providing supporting details, and concluding effectively. These structural components play a crucial role in developing a unified idea. Furthermore, students commonly made errors such as veering off-topic, including unnecessary sentences, and disrupting the chronological sequence of events in complex writing tasks. Students made errors in composing the supporting and concluding sentences of the paragraph because they lacked comprehension of the primary function of the topic sentence. Суралцагчдын англи хэлээр бичсэн цогцолборт хийсэн дүн шинжилгээ Хураангуй: Энэхүү судалгаа нь Монгол Улсын Боловсролын Их сургуулийн бакалаврын оюутнуудын бичсэн цогцолборын (догол мөр) бүтэц болон өгүүлбэрүүдийн нэгдмэл байдалд хийх дүн шинжилгээнд чиглэгдсэн болно. Судалгаа нь англи хэлний цогцолборын ерөнхийн бүтцийн хэсгүүдийг загвар болгон ашигласан. Судалгаанд нийт 6 оюутныг хамруулсан ба уг судалгааны мэдээлэлд оюутнуудын англи хэлээр бичсэн өөр өөр сэдэв бүхий цогцолбор багтсан болно. Судалгааны явцад оюутнууд цогцолборыг аливаа хэрэг явдлын тухай харьцангуй төгс санаа илэрхийлсэн нэгдмэл утга бүхий бүтэц гэдгийг ойлгодоггүй нь илэрсэн. Зарим оюутнуудын хувьд цогцолборын бүтцийг зөв зохион байгуулж бичих тал дээр бэрхшээлтэй тулгарч байв. Түүнчлэн оюутнууд цогцолбор бичихдээ тухайн сэдвээсээ хазайсан, онц чухал шаардлагагүй өгүүлбэрүүдийг бичих болон үйл явдлын дэс дарааллыг алдагдуулсан зэрэг алдааг гаргаж байсан. Оюутнууд цогцолборын дэмжих туслах болон дүгнэлт өгүүлбэрийг бичихдээ алдаа гаргаж байсан нь чиглүүлэгч өгүүлбэрийн гол үүргийг сайн ойлгоогүйтэй холбоотой байв. Түлхүүр үг: бичих чадвар, чиглүүлэгч өгүүлбэр, дэмжигч өгүүлбэр, дүгнэлт өгүүлбэр